Work Disability Associated with Cancer Survivorship and Other Chronic Conditions - Short, Pamela Farley (2008)
The long-term effects of cancer and its treatment on employment and productivity are a major concern for the 40% of cancer survivors in the U.S. who are working age. This study’s objectives were (1) to quantify the increase in work disability attributable to cancer in a cohort of adult survivors who were an average of 46 months post-diagnosis and (2) to compare disability rates in cancer survivors to individuals with other chronic conditions. Data from the Penn State Cancer Survivor Study (PSCSS) and the Health and Retirement Study (HRS) were compared. The PSCSS sample included 647 survivors age 55–65, diagnosed at four medical centers in Pennsylvania and Maryland. There were 5988 similarly aged subjects without cancer in the HRS. Adjusted odds ratios for work disability were estimated for cancer survivorship, heart disease, stroke, diabetes, lung disease, and arthritis/rheumatism with multivariate logistic regression. Even for cancer-free survivors, the disability rate was significantly higher in comparison to adults with no chronic conditions (female OR=1.94; male OR=1.89). There were few significant differences between disability rates for cancer and other conditions. The elevated disability rate is another argument for viewing cancer survivorship as a chronic condition potentially requiring a broad range of psychosocial services.